Analisis Kesalahan Berbahasa Dalam Menulis Naskah Pidato Di Sdn Talagasari Kecamatan Cikupa Kabupaten Tangerang - Akhmad Jaenudin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to describe language errors in writing speech scripts at SDN Talagasari, Cikupa District, Tangerang Regency in terms of spelling, affixes, reduplication, word waste and diction. The approach and type of research used in this study is qualitative descriptive. The data in this study is in the form of language errors in writing speech scripts at SDN Talagasari, Cikupa District, Tangerang Regency. The source of data for this research is the writing of speeches of grade VI students of SD Negeri Talagasari for the 2024/2025 school year. The data collection technique was carried out using the documentation method. After the speech script is read, the speech script is carefully scrutinized to find language errors that will be used as data. The researcher made a list of data variables then recorded each data found and grouped the data. in accordance with the aspects to be studied. The data analysis technique consists of three components, namely data reduction, data presentation, and conclusion drawn. This study uses a data validity check using a triangulation technique. In this case, the researcher uses data triangulation. In addition, this research is carried out through several stages, namely the pre-field stage, implementation, and research report. Based on the results of the research, several language errors were found in the writing of students' speeches. From the samples taken, the most common language errors found were spelling errors. In addition, affix errors, reduplication, word waste, and diction are also found in student essays. The results of the analysis of language errors in the writing of grade VI students of SD Negeri Talagasari, Cikupa District, Tangerang Regency for the 2024/2025 school year can be concluded as follows: (1) language errors that are often found in writing student speeches are spelling errors. Spelling errors occur due to improper writing of words, capital letters, italics, number symbols, and punctuation, (2) affix errors are found in the use of the prefix me-, prefix in-, confix se-, confix di–kan, and confix me- -kan (3) reduplication errors occur due to the use of incorrect reaffixes (4) word waste occurs because there are still many The use of words that actually do not need to be used (5) diction errors occur due to improper word selection